Моделирование поляризационно-оптических устройств с напряженными элементами - Тесленко, А. А. (НТУ "ХПИ", 2009)
На прикладі циліндра, стислого по діаметру, досліджена можливість моделювання проходження світла через довільну послідовність оптичних пристроїв, включаючи п'єзооптично активні напружені тіла. Як прийом моделювання визначений як відповідний засіб представлення тіла, як набору тонких пластин. Випробуваний найпростіший метод визначення оптимальної товщини пластин.

A possibility of modeling arbitrary optical devices sequence is investigated. The investigation is performed for cylinder compressed on diameter. Optical devices sequence can including piezooptic active, stressed bodies. The methods of modeling devices are determined. The bodies are presented as raw of thin plates. The thin plates was stressed arbitrary. Simple method of determination of optimum thickness of plates is tested.
Keywords: оптические материалы; компьютерное имитационное моделирование; напряженные тела; матрицы Джонса; матрицы Мюллера